Analisis Pengembangan Angkutan Bus sebagai Moda Transportasi untuk Pergerakan dengan Tujuan Pendidikan - Iswan Izzulhaq; Muhammad Yamin j; Venny Veronica Natalia (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2022)
Trip with the aim of education have a high level of contribution after working trip and become one of the activities that cause traffic congestion in Makassar City. Since November 2021, the South Sulawesi Provincial Transportation Service has introduced a bus service called Teman Bus with 2 of 4 service routes serving the Hasanuddin University educational area. This study aims to 1) determine the characteristics and patterns of educational movement of Unhas students, 2) analyze the availability and quality of bus transportation services, 3) formulate recommendations for the development of bus transportation as a mode of transportation for movement with educational purposes. The research method used is descriptive through a qualitative & quantitative approach using quantitative and qualitative descriptive analysis, Origin Destination Matrix (MAT) analysis, spatial analysis, and comparative analysis. The results of the analysis show that 1) 67% of Unhas students use private vehicles to move for educational purposes, the movement pattern of origin of Unhas students is concentrated in the area around the campus, while the rest are scattered in several sub-districts in Makassar City, Kab. Gowa and Maros. 2) The availability of bus transportation that serves the Unhas campus area consists of corridor 2 and corridor 4. Comparison of service quality between corridors 2 and 4 both have discrepancies in the quality of assessment for load factor and vehicle utility parameters. The recommended development recommendations are the development of feeder services, development of mode transfer nodes, improving the quality of bus stops, increasing mobility options using bus transportation and controlling and limiting the use of private vehicles.